Music theory - Miller, Michael (Indianapolis, Indiana : Alpha, a member of Penguin Random House LLC., 2016)
Explains the technical fundamentals of musical terminology, concepts, and principles; offers musical examples of scales, chords, intervals, and rhythms; and provides aural exercises for ear training and transcription skills
Includes bibliographical references and index
Keywords: Instructional and educational works; MUSIC Instruction & Study Theory